Dimensions of the diet-exercise relationship in later life: A qualitative study - Pettigrew, S.; Jongenelis, M.I.; Talati, Zenobia; Myers, G.; Sapountsis, Nina (2023)
Objective: Diet and physical activity are two lifestyle behaviours that are critical for healthy ageing. The aim of this study was to explore how older adults negotiate dietary and physical activity decisions to identify areas of intersection between these two behaviours and inform health promotion interventions targeting both diet and exercise. Methods: This exploratory study utilised a novel data collection approach that involved lay interviewers recruiting their peers to (i) participate in two interviews over a period of six months and (ii) make notes on their thoughts relating to diet and physical activity. Participants were 75 adults aged 60+ years in Western Australia (n = 64 females). Results: Three primary themes were identified: (i) the importance but difficulty of achieving energy balance; (ii) issues relating to managing food intake before, during, and after physical activity; and (iii) reciprocal opportunities for eating and physical activity. Conclusions: Diet and physical activity are linked in complex ways, highlighting the need for multi-factorial interventions. Implications for public health: When developing communications strategies designed to encourage older people to both improve their diets and increase their physical activity, consideration could be given to leveraging existing perceived alignments between healthy eating and being active.